Web-based application 'eAmplang' as an alternative promotion for MSME Amplang - Amiril Azizah; Karyo Budi Utomo; Zainal Arifin; Ratna Wulaningrum; Muhammad Aji Pangestu; Novia Rachmadyanti (Universitas Muhammadiyah Magelang, 2023)
Amplang MSME have difficulty promoting their products and need an alternative sales system as a promotional medium. As a solution, the service team developed a web-based application 'eAmplang'. Activities carried out by the process of designing applications, testing and publication through domains and hosting with the site https://amplang.eminat.store, as well as socialization of applications to MSME Sinar Terang and Nazwa. This application is very useful for expanding product marketing and product introduction to the public and supporting the sustainability of MSME businesses in digital competition.